Adaptation and Psychometric Evaluation of the Quality of School Life Scale in the Indonesian Educational Context - Istiqomah, Istiqomah; Wiyono, Bambang Budi; Rahmawati, Hetti; Chusniyah, Tutut (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
The quality of school life reflects students’ perceptions of satisfaction and well-being based on their positive and negative experiences in school settings. This study presents a psychometric adaptation of the Quality of School Life (QSL) scale into the Indonesian context—a crucial step, as no culturally validated version of this instrument previously existed in Indonesia. The study involved 203 high school students and utilized the adapted QSL scale for data collection via Google Forms. Confirmatory Factor Analysis (CFA) was used to evaluate the construct validity. The initial version included 29 items, but two items were excluded due to factor loadings below 0.40. The remaining 27 items showed factor loadings between 0.508 and 0.890. The model fit indices demonstrated satisfactory results (RMSEA = 0.048, CFI = 0.930, TLI = 0.923, SRMR = 0.077). The scale exhibited strong reliability, with Composite Reliability (CR) = 0.98 and Cronbach’s Alpha = 0.921. Content validity assessed by 12 expert judges yielded an Aiken’s V index of 0.79. Convergent validity was supported by AVE values above 0.50 in all dimensions, while discriminant validity was indicated by the square root of AVE exceeding inter-construct correlations—except for one dimension. These findings confirm the strong psychometric properties of the adapted instrument. The study contributes a culturally relevant and statistically validated tool for assessing students' school life quality in Indonesia, which can serve as a foundation for broader educational evaluation and policy improvement.